A study protocol to evaluate the impact of a personal and domestic hygiene intervention on lead exposure in a community next to a mine dump - Charlotte Mokoatle; Angela Mathee; Renee Street; Vusumuzi Nkosi (BMC, 2022)
Abstract Background Lead has been associated with adverse health effects, especially neurocognitive and behavioural effects, in children. Communities living close to mining land are at risk of elevated exposure to lead. Methods This paper outlines a before and after intervention study protocol to evaluate the impact of a personal and domestic hygiene intervention on lead exposure in a community located adjacent to a mine dump. In each participating household, parents or guardians will be interviewed using a structured questionnaire to obtain information on socio-demographic characteristics, living conditions, domestic hygiene practices and potential alternative sources of exposure to lead. A registered nurse will collect hand wipe samples from children aged one to five years, for whom parental consent and where possible child assent has been obtained. Environmental dust samples will be collected from the floors and/or windowsills of children's dwellings for lead content analysis. Soil samples will be collected from yards to determine lead content. An educational intervention will then be applied to the intervention group, including the engagement of households or guardians in an educational discussion on the sources, pathways of exposure, health effects of lead exposure and protective measures, with the aid of a specially designed educational brochure. Data will be analysed for descriptive and inferential statistics using Stata version 16. Discussion The study will determine whether the intervention led to a reduction in indoor dust lead levels, and if shown to be effective, will inform the development of an awareness campaign to reduce lead exposure in communities located in close proximity to mine dumps. Trial registration The study is retrospectively registered on ClinicalTrials.gov Protocol Registration and Results System with registration number NCT05265572 and first release date of 18th February 2022.